Challenges of DCFTAs: How can Georgia, Moldova and Ukraine succeed? - Amat Adarov; Peter Havlik (The Vienna Institute for International Economic Studies (wiiw), 2017)
The imbalance between the costs and benefits of DCFTAs is a call to the EU to display greater thoughtfulness and pragmatism if it does not want to lose support for reforms in its neighbourhood. What has to happen so that their potential can be more beneficial? The Policy Brief written by Amat Adarov and Peter Havlik in cooperation with Bertelsmann Stiftung discusses the policy implications of the agreements.
Keywords: 330; DCFTA; Association Agreement; EU Neighbourhood Policy; Georgia; Moldova; Ukraine; economic integration; policy impact evaluation